ANALISIS PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI ERA OTONOMI DAERAH (KESENJANGAN KEBIJAKAN, KURIKULUM, DAN KOMPETENSI GURU PAI) - Hidayatus Salehah; Puput Syahara Hibatullah; Haidir Rahmad; Ajahari Ajahari (Fakultas Tarbiyah IAI Darussalam, 2026)
Islamic Religious Education (IRE) has a strategic role in shaping students’ character and moral values in Indonesia. However, the implementation of IRE in the era of regional autonomy faces various problems, including policy gaps, curriculum issues, teacher competency, educational funding, and governance challenges. This article aims to analyze the problems and challenges of IRE in the decentralization era and to propose strategic solutions to improve its quality. This study uses a library research method by examining journals, books, regulations, and previous studies related to Islamic education and regional autonomy. The findings show that educational decentralization provides opportunities for local-based innovation but also creates disparities in educational quality among regions due to differences in resources, funding, and teacher quality. In addition, challenges related to digitalization, religious moderation, and the relevance of learning methods also affect the effectiveness of IRE. Therefore, strengthening regulations, equal distribution of teachers, digital transformation, and governance synergy are needed to improve the quality of IRE evenly across Indonesia.